The Enchanted Self: Individual Identity Change in Fiction and Film - Gordić Petković, Vladislava (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The paper will focus on the representations of identity, self, fantasy and transformation in seemingly incomparable novels and films. The theoretical background of the analysis is partly based on Laura Mulvey’s theory of “male gaze”, along with various critical analyses of other processes that radically change the concept of identity, love, emotion, and desire in the modern world. The novel The Enchanted April and the film Her show that the gap dividing the imaginary self and the real world narrows as the protagonists tread into beautiful landscapes as imaginary territories that bring miraculous change of personalities and relationships. In this paper, Theodore Twombly and Lady Caroline Dester are seen primarily as fugitives from their respective realities of the year 2025 and the 1920’s: while Theodore seeks solace in connecting to a computer operating system designed to function as a flawless emotional partner, Caroline retreats to a garden of a fascinating mansion San Salvatore in order to find her priorities and define her own identity, with the firm intention to become more than a beautiful object of male gaze and desire. The paper will explore the examples of hunger for intimacy in the modern age, as well as the human need to form romantic obsessive attachments to inanimate objects, places and landscapes.